Advances in digital management systems and smart applications - Mohtar, Syahida (Penerbit UTeM Press, 2025)
In today's rapidly evolving digital landscape, businesses, institutions, and industries must adapt to smarter, more efficient management systems. Advances in Digital Management Systems and Smart Applications presents cutting-edge research and practical insights into the latest innovations in digital management, cloud computing, business intelligence, and smart applications. This book serves as a valuable resource for researchers, industry professionals, and academics seeking to explore the intersection of technology, innovation, and efficiency in digital management. By offering analytical insights and real-world applications, it equips readers with the knowledge to navigate and contribute to the ever-evolving landscape of smart systems and data-driven decision-making.